2007
DOI: 10.1007/s10704-008-9195-5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of void linkage in model materials using a nonlocal ductile damage approximation

Abstract: Experiments on the growth and linkage of 10 urn diameter holes laser drilled in high precision patterns into Al-plates were modelled with finite elements. The simulations used geometries identical to those of the experiments and incorporated ductile damage by element removal under the control of a ductile damage indicator based on the micromechanical studies of Rice and Tracey. A regularization of the problem was achieved through an integral-type nonlocal model based on the smoothing of the rate of a damage in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Immediately before fracture (8.9% strain), the minimum dNN is 3.2 m. Finite element analysis has revealed that the stress intensity between nanovoids is significantly enhanced when the distance between them is less than five times the nanovoid diameter [51]. As the mean nanovoid diameter is 2.5 × 10 −7 m, dNN must be ≤1.25 m to generate a linkage.…”
Section: Influence Of Nanovoids On the Fracturementioning
confidence: 99%
“…Immediately before fracture (8.9% strain), the minimum dNN is 3.2 m. Finite element analysis has revealed that the stress intensity between nanovoids is significantly enhanced when the distance between them is less than five times the nanovoid diameter [51]. As the mean nanovoid diameter is 2.5 × 10 −7 m, dNN must be ≤1.25 m to generate a linkage.…”
Section: Influence Of Nanovoids On the Fracturementioning
confidence: 99%
“…Gunawardena [8] developed a damage model on the basis of Rice and Tracey model. Assuming spherical growth of voids and rigid-plastic behavior of materials, the fracture reference strain ε f is calculated for different states of stress triaxiality as follows:…”
Section: Gunawardana Modelmentioning
confidence: 99%
“…Regardless of the different techniques used to characterize the damage evolution with equations and some parameters, it primarily relies on the test data curve to fit the empirical void/damage evolution function. Examples include the Gurson-Tvergaard-Needleman (GTN) model [2], Rice-Tracey model [3], Gunawardena model [4], the well-known, strain rate dependent Johnson-Cook (J-C) damage model [5], some micro-mechanism based damage models, and models using irreversible entropy as a metric with an empirical evolution function. These empirical models are popular for engineering applications due to their simplicity.…”
Section: Introductionmentioning
confidence: 99%